Remanufacturing and advanced machining processes for new materials and components. (2022) - Gevorkyan, E. S; Rucki, M; Nerubatskyi, V.P; Żurowski, W; Siemiątkowski, Z; Morozow, D; Kharatyan, A.G
No abstract available